ROOTING OF WOODEN CUTTINGS OF PEACH CV. MARFIM BY DIFFERENT IBA CONCENTRATION - MINDÊLLO NETO, Ubirajara Ribeiro; TORRES, André Nunes Loula; HIRANO, Elcio (Scientia Agraria, 2004)
This work was carried out in mistchamber at EMBRAPA Technology Transference at Canoinhas-SC with aim to evaluate the effect of indolbutyric acid (IBA) on rooting of wooden cuttings of peach cv. Marfim. Wooden cuttings were treated with IBA at different concentrations (0, 100, 500, 1.000 and 5.000 mg.L-1) and planted in expanded polyestirene trays with 72 cells, with medium granulometric sand as substrate. It were evaluated percentage of rooted cuttings, percentage of dead cuttings and the number of roots per cuttings. The three analised characteristics showed a quadratic effect with crescent concentrations of IBA. The concentration of IBA wich presented highest rooting was 2.966 mg.L-1 with 81,92% of rooted cuttings. The concentration of IBA wich presented lowest dead root and highest number of roots were 3.075 and 2.941 mg.L-1 respectively.